PERANAN KEPEMIMPINAN KEPALA SEKOLAH, MOTIVASI KERJA, DAN BUDAYA SEKOLAH DALAM UPAYA PENINGKATAN KINERJA GURU DI SMK SWASTA KECAMATAN WONOSOBO, KABUPATEN WONOSOBO (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This research is aiming for understanding The Role of Headmaster Leadership, Working Motivation and School Culture in the effort of Improving Teacher Work, in Private Vocational High School in Wonosobo Sub-district, Wonosobo Regency.This research is correlative that is finding the relation between variables which is shown by the number of correlation co efficient. The data is taken from the sample that is Private Vocational High School teachers in Wonosobo Sub-district, Wonosobo Regency, Central Java. The data resource is taken from 125 samples. The technique of data collecting uses questionnaire instrument. Analysis technique uses double regression technique with three predictors. Hypothesis test collectivity uses F test or ANOVA test continued by individually hypothesis test with partial test. The data is tested by using requirement tests, they are normality test, linearity test multi co linearity test with significance grade is 5%.According to research result, it can be concluded that : (1) it is collectivity thet Role of of Headmaster Leadership, Working Motivation and School Culture in the effort Improving Teacher Work, in Private Vocational High School in Wonosobo Sub-district, Wonosobo Regency, (2) it is separately that headmaster leadership play a significantly positive role in the effort of Improving Teacher Work, in Private Vocational High S